Efektifitas Penggunaan Kompres Hangat Terhadap Nyeri Persalinan Pada Ibu Bersalin Kala1 Di Bpm Umrotul Ustadah Amd.Keb Dawar Blandong Mojokerto - Yulianti, Indra; Artiningsih, Ninik (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractLabor is a physiologist event in every development of a woman being a mother. This event can cause trauma to the mother because of labor pain. One of the non-pharmacological methods to reduce labor pain is to provide warm compresses that aim to meet the needs of comfort, reduce or relieve pain, prevent muscle spasms, and provide a sense of warmth. The purpose of this research is to know the effectiveness of the use of warm compresses against the labor pain at the maternity mother kala 1 in bpm umrotul ustadah UR amd.keb dawar blandong mojokerto. The design of this research is lo approach pre-Ekperimental with pretes-postest design. Variables in research that is warm compresses as the independent variable and the dependent variable as a labor pain. Research population that is as much as 8 respondents and samples taken with the accidental sampling techniques. Data taken using a warm compress observation sheet instruments and observation sheet labor pain using the measuring instrument Bourbanais Scale value. Based on statistical tests are performed using test wilxocon _J = 0.023 results of this research show that there are influences of the scale of pain after being given a warm compress where this sign as seen from changes of scale of pain before given a warm compress, while after being given a warm compress for 10-15 minutes, and the respondents are already reduced to not seem in pain again. It can be noted that there is the effectiveness of the use of warm compresses against the labor pain at the maternitymother kala 1.Key Words: Wann Compress, Pain